2016
DOI: 10.3748/wjg.v22.i6.2060
|View full text |Cite
|
Sign up to set email alerts
|

hsa-miR-29candhsa-miR-135bdifferential expression as potential biomarker of gastric carcinogenesis

Abstract: Our results provide evidence of epigenetic alterations in non-atrophic chronic gastritis and intestinal metaplasia and suggest that hsa-miR-29c and hsa-miR-135b are promising biomarkers of gastric carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 51 publications
3
35
0
Order By: Relevance
“…Some findings have suggested that there is an elevation in miR-135b expression in clinical samples compared with the corresponding epithelium; the average expression of miR-135b in GC tissues was notably higher than in the normal epithelium (25). Moreover, hsa-miR-135b has been identified as a promising biomarker for gastric carcinogenesis because its expression has been found to be up-regulated in gastric lesions compared with normal gastric mucosa and intestinaltype gastric adenocarcinoma samples (17). A previous study concluded that MST1 and cyclophilin D expressions were notably reduced in gemcitabine-resistant pancreatic cancer tissues and cell lines (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some findings have suggested that there is an elevation in miR-135b expression in clinical samples compared with the corresponding epithelium; the average expression of miR-135b in GC tissues was notably higher than in the normal epithelium (25). Moreover, hsa-miR-135b has been identified as a promising biomarker for gastric carcinogenesis because its expression has been found to be up-regulated in gastric lesions compared with normal gastric mucosa and intestinaltype gastric adenocarcinoma samples (17). A previous study concluded that MST1 and cyclophilin D expressions were notably reduced in gemcitabine-resistant pancreatic cancer tissues and cell lines (24).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies suggest that a correlation exists between MST1, miR-135b, and the MAPK signaling pathway with GC (16)(17)(18). However, the exact mechanism of the interaction has yet to be thoroughly investigated.…”
Section: Methodsmentioning
confidence: 99%
“…Increasing studies have revealed that the dysregulation of miRNAs is strongly associated with the tumorigenesis and progression of cancers, including GC [16-18]. Additionally, miRNAs have been reported to be used as biomarkers of diagnosis [19] and prognosis [20, 21] in GC.…”
Section: Discussionmentioning
confidence: 99%
“…Only around 2% of all transcripts (mRNA) are translated into protein, and mounting evidence suggests that the noncoding transcripts (ncRNA), such as short RNA, miRNA, piRNA and more, are as important as mRNAs. For example, micro‐RNA hsa‐miR‐29c is progressively downregulated according to the pathological stages: normal gastric mucosa, nonatrophic chronic gastritis, intestinal metaplasia, and intestinal‐type gastric adenocarcinoma . The DNA methyltransferase 3A, whose expression is increased in gastric cancer, has been implicated.…”
Section: Insights Into the Role Of Noncoding Rnasmentioning
confidence: 99%
“…For example, micro-RNA hsa-miR-29c is progressively downregulated according to the pathological stages: normal gastric mucosa, nonatrophic chronic gastritis, intestinal metaplasia, and intestinal-type gastric adenocarcinoma. 59 The DNA methyltransferase 3A, whose expression is increased in gastric cancer, has been implicated. The upregulation of hsa-miR-135b hints at a function as an onco-miR by acting through its two targets KLF4 and APC.…”
Section: Insights Into the Role Of Noncoding Rnasmentioning
confidence: 99%